Actualidad en Asia (2015)
This section is carried out by the student members of the hotbed of research in Asia Pacific of EAFIT University. Within this you can find three articles: What I Talk About When I Talk about Murakami, made by student Aurora Echeverri; Fairs of Asia, made by Manuela Vásquez and a special of the main news of the radio program Asia Pacific Contact.